Antineoplastic Agents 515. Synthesis of Human Cancer Cell Growth Inhibitors Derived From 3,4-Methylenedioxy-5,4′-dimethoxy-3′-amino-Z-stilbene - Pettit, George R. (2005)
Further structure-activity relationship (SAR) exploration of 3,4-methylenedioxy-5,4′-dimethoxy-3′-amino-Z-stilbene (1a) derivatives resulted in the efficient synthesis of tyrosine amide hydrochloride 9, two tyrosine amide phosphate prodrugs (3a and 6), and sodium aspartate amide 11. Two additional cancer cell growth inhibitors (14 and 16) were synthesized by employing peptide coupling between amine 1a and the Dap residue of dolastatin 10 (4a) to yield amide 14 followed by Dov-Val-Dil (15) to yield peptide 16. The latter represents a combination of stilbene 1a with the des-Doe tetrapeptide unit of the powerful tubulin assembly inhibitor dolastatin 10. Peptide 16 was examined for potential binding to tubulin in the vinca and/or colchicine regions and found to perform primarily as a relative of dolastatin 10. Amide 14 had anticryptococcal and antibacterial activities.